Pyroelectric dependence of atomic layer-deposited Hf0.5Zr0.5O2 on film thickness and annealing temperature - Lomenzo, Patrick D.; Alcala, Ruben; Richter, Claudia; Li, Songrui; Mikolajick, Thomas; Schroeder, Uwe (Applied physics letters, 2021)
Ferroelectric Hf0.5Zr0.5O2 is a prime candidate material for integrated HfO2-based ferroelectric devices due to its simple composition, low crystallization temperature, and significant remanent polarization. It is particularly promising for integrated pyroelectric devices used in infrared sensing and energy harvesting, although the appearance of nonferroelectric tetragonal and monoclinic phases should be avoided to achieve high-performance pyroelectric sensors. Both nonferroelectric phases are strongly influenced by the Hf0.5Zr0.5O2 film thickness and annealing temperature. The sensitivity of the pyroelectric coefficient on film thickness is investigated with atomic layer-deposited Hf0.5Zr0.5O2 films within a 10–30 nm thickness range. The films are capped with TiN and undergo post-metallization anneals at 450 °C and 600 °C. An optimum pyroelectric coefficient of −56 μC K−1 m−2 is found in the 15 nm thick Hf0.5Zr0.5O2. The pyroelectric coefficient is found to be sensitive to thickness-dependent depolarization effects and monoclinic phase growth. Ferroelectric, dielectric, and pyroelectric properties are improved with a lower annealing temperature, demonstrating the back-end-of-line compatibility of Hf0.5Zr0.5O2 pyroelectric devices.